Status Hukum Perjanjian Beli Kembali (Buy-Back Guarantee) yang Diberikan oleh Developer Pailit kepada Bank - Tyas, Hesti Ning; Sukarmi, Sukarmi; Audrey, Patricia (Universitas Negeri Malang, 2022)
This study analyzed the contract disputes in the Supreme Court Decision Number 1013K/Pdt.Sus-Pailit/2016 and the legal status of the buy-back guarantee agreement obtained from the bankrupt developer. This study used a normative juridical method with a statutory approach and a conceptual approach. The contract dispute in the Supreme Court Decision Number 1013K/Pdt.Sus-Pailit/2016 related to submitting several claims based on the buy-back guarantee agreement between PT. Bank Mandiri (Persero) Tbk. as a creditor with PT. Rizky Jaya Sentosa Ladang was the developer who was declared bankrupt when the debtor defaulted. The legal status of the buy-back guarantee agreement obtained by the bank from the bankrupt developer remained binding on the parties who have agreed. The contents of the buy-back guarantee agreement remained valid as law for the parties because one of the bankrupt parties was not included in the conditions for the termination of engagements and agreements.